Neighborhood in the west and the soviet microdistrict: Implementation of related ideas in various social systems (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The article presents a comparative analysis of two modernist models of residentialenvironment organization that emerged in the first third of the 20th century: based on relatedplanning units – the Western “neighbourhood unit” and the Soviet microdistrict. Both emerged asresponses to the universal challenges of industrial urbanization – the housing crisis, acceleratedurban growth, transport conflicts and the need to ensure everyday functions within pedestrianaccessibility – but developed in fundamentally different political and institutional systems. Thepaper examines whether these models were parallel responses to common challenges, whether therewas a direct or indirect mutual influence between them, and determines the universality andcontextual conditionality of their implementation.An attempt is made to identify similarities and differences in the processes of emergence andtransformation of the neighbourhood and microdistrict, as well as possible relationships betweenthem. The evolution of the "neighbourhood unit" in the United States is examined, from the earlyworks of W. E. Drummond to its normative formulation by C. A. Perry in 1929 in the concept ofthe Regional Plan of New York and its environs; the role of British experience in the formation ofsocially oriented planning, in particular the activities of T. Adams and the Russell Sage Foundation,is outlined. A system of key planning principles of the "neighbourhood unit" is identified (borderinghighways, eliminating transit, centricity of schools and public functions, a system of open spaces).In parallel, the genesis of the Soviet microdistrict is analysed: the developments of the“Dipromisto” institute in the 1930s under the leadership of O. Eingorn, the change in approaches inthe post-war period, the normative restoration of the microdistrict principle in the second half of the1950s and its large-scale implementation until the beginning of the 1990s, including subsequentmodifications (the “focusing” method of L. Tulpa). It is shown that the similarity of the initialproblems caused the similarity of a number of planning principles, however, differentimplementation mechanisms – experimental-developmental in the West and centralized-normativein the USSR – determined different development trajectories and practical effects of these models.
Keywords: neighbourhood; neighbourhood unit; microdistrict; garden city; urban planning concepts; planning principles; modernism